2007
DOI: 10.1207/s15374424jccp3601_5
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Aggressive Influences and Children's Aggressive Problem Solutions With Peers

Abstract: This study examined children's aggressive and assertive solutions to hypothetical peer scenarios in relation to parents' responses to similar hypothetical social scenarios and parents' actual marital aggression. The study included 118 9−10 year old children, and their mothers and fathers. Children's aggressive solutions correlated with same-sex parents' actual marital aggression. For children with mothers who exhibit low actual marital aggression, mothers' aggressive solutions to hypothetical situations corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 50 publications
2
14
1
1
Order By: Relevance
“…In a study involving 7‐ to 13‐year‐old children, Marcus, Lindahl, and Malik (2001) found that children's aggressive problem‐solving solutions mediated the relation between interparental conflict and children's aggressive behavior at school but not their aggressive behavior at home. Finally, Duman and Margolin (2007) discovered that children's aggressive problem‐solving strategies corresponded with same‐gender parents' reported marital aggression. To this point, no published studies have examined child social problem solving in mediating the link between marital conflict and child peer competence.…”
Section: Social Information Processing Theorymentioning
confidence: 99%
“…In a study involving 7‐ to 13‐year‐old children, Marcus, Lindahl, and Malik (2001) found that children's aggressive problem‐solving solutions mediated the relation between interparental conflict and children's aggressive behavior at school but not their aggressive behavior at home. Finally, Duman and Margolin (2007) discovered that children's aggressive problem‐solving strategies corresponded with same‐gender parents' reported marital aggression. To this point, no published studies have examined child social problem solving in mediating the link between marital conflict and child peer competence.…”
Section: Social Information Processing Theorymentioning
confidence: 99%
“…Children learning can take place through observation of actions modeled by their parents, and through the application of reward/punishment system to reinforce specific behavior. Based on these facts, it does not ease to understand how consistent discipline and parental displays of warmth could foster adaptive socioemotional skills, while tough, inconsistent, or furious parenting may facilitate undesirable behaviors in children [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Maccoby (1996) highlighted the need for a "conceptual bridge" between intrafamily conflict and peer conflict. mothers' as well as fathers' marital aggression as important influences in children's aggressive problem solving ( e.g., Duman & Margolin, 2007). In order to improve individual development and social acceptance, it is necessary for programs that support important competence skills such as analyzing the problems in interpersonal relations in a way in which both parties win, self-regulation, social competence, adaptive behavior, decision-making and resiliency to be started in the pre-school period with early training programs.…”
Section: Discussionmentioning
confidence: 99%